LEACHING THE LEAD FROM ANODE SLIME BY AMMONIUM ACETATE SOLUTION - Isyatun Rodliyah; Ngurah Ardha; Nuryadi Saleh; M. Zaki Mubarok (Indonesian Mining Journal, 2011)
Selective leaching the lead from anode slime from PT. Smelting (PTS) was investigated. The presence of large amount of lead in electrometallurgical anode slime courses of extraction of precious metals (Au, Ag) and other valuable metals (Bi, Se, Te, Pt and Pd) from the slime is more difficult. A process for taking off lead content in anode slime was subjecting the latter to first and second-stage leaching in a medium of an ammonium acetate solution at temperature not exceeding 80°C. Whereby lead dissolution is maximized and other metals are minimized. The effects of various parameters such as solvent concentration, leaching time, temperature, and solid/liquid ratio on the percent extraction of lead were studied. The highest recovery of lead is attained 94.9% Pb at the leaching temperature of 70°C, solvent concentration of 8 M and percent solid 20% after 120 minutes of leaching time. The leaching kinetics of lead sulfate in an ammonium acetate solution followed the ash diffusion control model and this further confirms that the activation energy of leaching is found to be 4.8 kcal/mol, to show that rate reaction can increased by mixing.